Natural Approach or Cognitive Approach. Learning or Acquiring a Foreign Language? Research Study at Centro de Lenguas de la Universidad Autónoma de Ciudad Juárez - Serrano Romero, Enriqueta Claudia (2019)
There is a big dilemma among instructors teaching English as a foreign language. Competence and teaching grammar rules are the primary pedagogical concern. Competence is directly related to the ability of proper grammar use of a language. However, methodological discussions end up accepting that grammatical rules are neither sufficient nor demonstrating the acquisition of the language. Learner students may have correctly learned grammatical rules, but some studies disagree on teaching only grammar because it will not ve enough for students to speak forcefully. These circumstances lead to the discussion on the English Teaching method used at the Autonomous University of Ciudad Juárea (UACJ).